​ Features of motivation of professional self-determination of modern teenagers (Actual Problems of Psychology in Educational Institutions, 2019)
​ In the article the processes of development of motivation in thecontext of age development of the personality of adolescents are considered.The issues of personal and professional self-determination in adolescence areexplored. The role of motivation in its structure is determined. The typology ofprofessions is considered. The adolescence as an important transitional period inthe development of motivation to professional self-determination is explored.The results of the empirical study of the characteristics of the motivation ofmodern adolescents to choose a profession, in particular, on account of thecomplex of their cognitive interests, are presented. Psychological andpedagogical references for teachers and parents concerning development ofmotivation for professional self-determination of adolescents are developed.